Perceived racial/ethnic discrimination, marketing, and substance use among young adults. Issue 4 (2nd October 2019) - Rose, Shyanika W.; Mayo, Ashley; Ganz, Ollie; Perreras, Lexie; D'Silva, Joanne; Cohn, Amy
ABSTRACT: Perceived experiences of discrimination have been linked to negative health behaviors including tobacco, alcohol, and marijuana use across various racial/ethnic groups. Tobacco and alcohol marketing exposure have also been linked with substance use. This study examined the independent and interacting effects of perceived experiences of discrimination and exposure to alcohol and tobacco marketing, and receptivity to marijuana marketing on substance use in an online survey of a multiethnic sample of young adults in 6 metropolitan areas ( n  = 505). African Americans (mean ( M ) = 1.96, 9% 5CI [1.84, 2.09]) and Hispanics ( M  = 1.98, 95% CI [1.87, 2.09]) reported higher levels of perceived discrimination than Whites ( M  = 1.52, 95% CI [1.40, 1.64]), p  <  .001. African Americans had higher levels of exposure to tobacco and alcohol marketing; Hispanics reported higher levels of exposure to alcohol marketing and receptivity to marijuana promotion. Discrimination and marketing exposure were independently associated with higher odds of all 3 outcomes, controlling for covariates (AOR from 2.1 to 3.4 for discrimination; AOR from 1.4 to 13.8 for marketing). Models showed a significant interaction of discrimination and tobacco marketing on past 30-day cigarette use (F = 5.5; p  = .02). Individuals with high levels of tobacco marketing exposure were likely to report high past 30-day cigarette use regardless of level of discrimination, while those with low exposure were only at increased risk of reporting cigarette use at higher levels of discrimination. Both perceived discrimination and marketing exposure play a role in substance use. Interventions should consider discrimination as a significant risk factor underlying vulnerability to substance use among young adults.